Hutan Lindung Wehea - Fajri, Muhamad; Shufi, Muhammad; Putra, Muhammad Wahyu Dwi; Sampoerna, Muhammad Indiana Putra; Malikusysyarqiy, A. Al-Faris; Andri, Syainal; Sari, Yosinta; Ahmad, Istiqomah; Muliana, Heni; Pamela, Ratri Cahya (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Forests are ecosystems containing biological resources, primarily dominated by trees, that are interconnected and inseparable from their environment. Communities hold both the rights and responsibilities for forest management, as their livelihoods heavily depend on forests. One example of an indigenous community that continues to uphold traditional forest management based on local wisdom is the Dayak Wehea Indigenous People in Nehas Liah Bing Village, Muara Wahau District, East Kutai Regency. This study aims to explore the role and efforts of the Dayak Wehea community in preserving forest sustainability. The research employs a qualitative method with data collection techniques including observation, interviews, and documentation. The findings reveal that the Wehea Indigenous People have successfully preserved their forests through cultural values and local wisdom, despite facing various challenges such as economic pressures, limited external support, and low youth participation. This success demonstrates that environmental conservation relies not only on technology and government regulations but also on the empowerment of local communities, respect for ancestral values, and a strong spirit of mutual cooperation.